Break us - Brown, Jennifer, 1972- (New York, NY : Katherine Tegen Books, an imprint of HarperCollinsPublishers, 2018)
"Nikki Kill doesn't see the world in black and white. Her synesthesia shades everything in view, transforming numbers, words, and emotions into colorful clues. Which means she's a dangerous commodity to anyone with something to hide. Nikki has already taken on the Hollises--one of L.A.'s most powerful families--for murdering her half sister, Peyton. However, Nikki's next steps are clouded by the gray of uncertainty. Before she knows it, Nikki is on the trail of a cold case that couldn't be any more personal--the death of her mother. But when the web of lies and secrets she uncovers leads back to the people who have tried to silence her, Nikki must pursue the sunbeam gold of justice, or everything--including her life--will be lost."--Amazon.co.uk.
Keywords: Synesthesia -- Juvenile fiction; Murder -- Investigation -- Juvenile fiction; Cold cases (Criminal investigation) -- Juvenile fiction; Synesthesia -- Fiction; Secrets -- Fiction; Murder -- Investigation -- Fiction; YOUNG ADULT FICTION / Family; YOUNG ADULT FICTION / Mysteries & Detective Stories; YOUNG ADULT FICTION / Romance / Contemporary; Cold cases (Criminal investigation); Murder -- Investigation; Synesthesia; Young adult fiction; Detective and mystery fiction; Fiction; Young adult works; Mystery fiction; Detective and mystery fiction